Study on methods to counter-measure IEEE 802.11 standard Wifi signals below 6 GHz - Triều, Lê Hải; Kiên, Trương Chí; Hiền, Ngô Thu (Journal of Science and Technology on Information security, 2023)
Abstract—Launched in 1980 according to the IEEE 802.11 standard, Wifi (Wireless Fidelity) wireless network supports the expansion of wired networks and has gradually become an important component of telecommunications infrastructure in society. Currently, Wifi network infrastructure is becoming increasingly important as its application has helped quickly connect to information sources, capture events and news effectively. However, the Wifi network has been exploited to conduct espionage, terrorism, sabotage, and criminal acts such as illegally collecting information, locating relatively accurate locations, and controlling remotely, illegally collecting information, terrorist attacks, especially distorted propaganda and incitement against the Party and Government of Vietnam by hostile forces and criminal organizations that affect national security, causing information insecurity that frequently occurs in sensitive event protection areas. In this article, the authors focus on researching a number of methods to jam Wifi signals in sensitive event protection areas to propose the most appropriate solution to promptly handle and prevent incidents from occurring bad situations arise.